2002
DOI: 10.1159/000048665
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Inflammatory Response System in Autism

Abstract: Background/Aim: There is now some evidence that autism may be accompanied by abnormalities in the inflammatory response system (IRS). Products of the IRS, such as proinflammatory cytokines, may induce some of the behavioral symptoms of autism, such as social withdrawal, resistance to novelty and sleep disturbances. The main aim of the present study was to examine whether autism is accompanied by an activation of the IRS. Methods: We measured the production of interleukin (IL)-6, IL-10, the IL-1 receptor antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(171 citation statements)
references
References 33 publications
8
159
2
2
Order By: Relevance
“…Vargas et al (2005) likewise showed the presence of an active neuroinflammatory environment, finding higher levels of MCP-1, TGF-β, and IL-6 in the brains of autistic patients. Of particular note is that many of the above studies found no increase in the Th2 cytokine IL-10 (Croonenberghs et al, 2002a;Krakowiak et al, 2015;Li et al, 2009;Molloy et al, 2006).…”
Section: Immune Dysregulationmentioning
confidence: 86%
See 1 more Smart Citation
“…Vargas et al (2005) likewise showed the presence of an active neuroinflammatory environment, finding higher levels of MCP-1, TGF-β, and IL-6 in the brains of autistic patients. Of particular note is that many of the above studies found no increase in the Th2 cytokine IL-10 (Croonenberghs et al, 2002a;Krakowiak et al, 2015;Li et al, 2009;Molloy et al, 2006).…”
Section: Immune Dysregulationmentioning
confidence: 86%
“…A 2006 study showed increases in the anti-inflammatory Th2 cytokines IL-4, IL-5, and IL-13 from PHA-stimulated PBMCs (Molloy et al, 2006), which was supported by a later study that indicated a Th2-like response was present at birth and connected increased IL-4 to more severe autism . On the other hand, a 2002 study demonstrated an increase in the blood cytokines IL-1RA and IFN-γ, suggesting a more Th1-like, proinflammatory response (Croonenberghs et al, 2002a), while a mouse model in 2007 showed Th1-skewed T-cell development in amniotic fluid alongside stereotypies in the offspring following treatment of pregnant dams with IL-2 (Ponzio et al, 2007).…”
Section: Immune Dysregulationmentioning
confidence: 99%
“…This possibility further leads to a notion that some highly toxic autoantibodies (as proposed in a few CSF samples from MRL-lpr mice) may have long-lasting consequences on behavior. The increased prevalence of autism spectrum disorders is a novel medical conundrum which involves autoreactivity to brain antigens (Todd et al, 1988;Singh et al, 1998Singh et al, , 2002Silva et al, 2004) and other autoimmune phenomena (Singh and Rivas, 2004;Sweeten et al, 2003;Croonenberghs et al, 2002). Together with immunological changes in schizophrenia spectrum disorders (Jones and Cannon, 1998) and epilepsies (Rogers et al, 1996), the above correlations beg for a deeper understanding of the relationship between autoimmunity and the developing brain.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports that children with ASD have abnormalities in the peripheral blood cells and cytokines that mediate both innate and adaptive responses (Connolly et al, 1999;Croonenberghs, Bosmans, Deboutte, Kenis, & Maes, 2002a;Gupta, Aggarwal, Rashanravan, & Lee, 1998;Jyonouchi, Sun, & Itokazu, 2002;Singh, 1996;Warren, Foster, & Margaretten, 1987). Within the adaptive immune response, elevated levels have been reported for both T H 1 cytokines, commonly seen in autoimmune disorders (Singh, 1996), and T H 2 cytokines, as seen in atopic diseases (Gupta, Aggarwal, & Heads, 1998).…”
Section: Pervasivementioning
confidence: 99%